Ilmu Mantra dalam amalan masyarakat Melayu science of Mantra practiced by the Malays - Yusri Mohamad Ramli (Penerbit Universiti Kebangsaan Malaysia, 2024)
Mantra śāstra is a tantric science that involves knowledge and methods related to word and speech. Although it is to some degree religious in connection with being a tool to communicate with the divine within Hindu and Buddhist traditions, the ancient Malays have a very intense attitude towards its practical aspect. The invention of a huge number of poetical genres as well as the prevalence of incantation in traditional medicine shows a very strong mastery of mantric skills. The technical aspect offered by these arts shaped the very skillful competency in language and literature among the Malays. This article is an attempt to explore to what extent the science of mantra is already been practiced in the past among the Malays.